Immigrants' Effect on Native Workers: New Analysis on Longitudinal Data - Mette Foged; Giovanni Peri (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2015)
Using longitudinal data on the universe of workers in Denmark during the period 1991-2008 we track the labor market outcomes of low skilled natives in response to an exogenous inflow of low skilled immigrants. We innovate on previous identification strategies by considering immigrants distributed across municipalities by a refugee dispersal policy in place between 1986 and 1998. We find that an increase in the supply of refugee-country immigrants pushed less educated native workers (especially the young and low-tenured ones) to pursue less manual-intensive occupations. As a result immigration had positive effects on native unskilled wages, employment and occupational mobility.
Keywords: F22; J24; J61; 330; Refugees; dispersal policy; manual skills; employment; wages